Pengaruh Perbandingan Modified Cassava Flour (Mocaf) dan Tepung Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Makaroni - Febriyani, Debora; Ayu Ekawati, I Gusti; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i01.p06, 2022)
This study was conducted with the aims to determine the effects of mocaf and red bean flour ratio on the characteristics of macaroni and determine the right ratio of mocaf and red bean flour which produces macaroni with the best characteristics. The experimental design used was Completely Ramdomized Design (CRD) with the ratio of mocaf and red bean flour consisted of 5 treatments namely: 90%:10%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%. Treatments were repeated 3 times to obtain 15 units of experiment. The data were analyzed with Analysis of Variance and if the treatment had significant effect then followed by Duncan’s Multiple Range Test (DMRT). Ratio of mocaf and red bean flour had significant effect on water content, ash content, protein content, crude fiber content, color (scoring), taste (hedonic and scoring) and overall acceptance (hedonic). Ratio of 70% mocaf and 30% red bean flour had the best characteristics with 5.59% water content, 2.28% ash content, 11.07% protein content, 18.67% crude fiber content, white brownish and liked color, rather liked aroma, liked texture, distinct red bean and rather liked taste, and liked overall acceptance.